Revisiting the linkage between remittances inflow and economic growth: A semi-parametric estimation with panel data - Arafet Farroukh; Manel Mazioued; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
We investigate the relationship between remittances inflow and economic growth in a sample of 65 emerging countries over the period 1988-2018 using the semi-parametric panel data model with fixed effects as proposed by Baltagi and Li (2002). Our empirical results show that the effect of remittances inflow on economic growth exhibits a highly nonlinear pattern, which sheds new light on the remittances-growth nexus and provides evidence of a nonlinear relationship.
Keywords: C14; O15; F43; 330; Remittances; Growth; Nonlinear effects; Semi-parametric regression; Panel data; Emerging countries